A relação entre lei, delitos e pena em Hegel - Berti, Márcio Guedes (2017)
The line of work followed in this dissertation approached the Hegelian concept of the theory of the punishment, from the point of view of Hegel’s Elements of the Philosophy of Right (EPR, 2010). To specifically deal with the aforementioned subject, tackling other concepts brought up by Hegel in EPR was deemed necessary, chiefly the notion of will and the unjust, being this the necessary course for the understanding of the Hegelian proposal of the theory of punishment. It was also intended to bring the concept of the Hegelian theory of punishment to the present day, establishing a dialogue between the theory of punishment proposed by Hegel and the contemporary Criminal Law. This paper approached the structure of the Hegelian Philosophy of Right, after which it dealt with the concept of will and its significance, the concept of person and the objective specificities of will. Subsequently, the unjust was analysed in its various modes, namely: good faith leading to injustice, fraud, violence and crime, and emergency law, to, then, analyse the theory of punishment, a point in which the paper tackles the purpose of punishment from the perspective of punishment as retribution (negation of the negation), of punishment as liberation of the individual, culminating in an analysis of the Hegelian theory of punishment and contemporary Criminal Law. The paper also brings back the ideas of intent (knowledge of wrongdoing) and guilt in the Hegelian morality with the aim understanding how laws are formed and how they become effective in society; what they are and what their purpose is.